2022
DOI: 10.3390/ijerph19159196
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment on Serious Adverse Events of Targeted Therapeutic Agents Prescribed for RAS Wild-Type Metastatic Colorectal Cancer: Systematic Review and Network Meta-Analysis

Abstract: Despite substantially elevated risk of serious adverse events (SAEs) from targeted therapy in combination with chemotherapy, comprehensive pharmacovigilance research is limited. This study aims to systematically assess SAE risks of commonly prescribed targeted agents (bevacizumab, cetuximab, and panitumumab) in patients with rat sarcoma viral oncogene homolog (RAS) wild-type metastatic colon cancer. Keyword searches of Cochrane Library, Clinical Key and MEDLINE were conducted per PRISMA-NMA guidelines. Frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…After surgery, chemotherapy can be administered to kill any remaining cancer cells and reduce the risk of cancer recurrence. The National Comprehensive Cancer Network (NCCN) guidelines recommend the use of chemotherapy regimens, including CAPOX (capecitabine and oxaliplatin), FOLFIRI (folinic acid, fluorouracil, and irinotecan), FOLFOX (folinic acid, fluorouracil, and oxaliplatin), or FOLFOXIRI (folinic acid, fluorouracil, oxaliplatin, and irinotecan), for unresectable metastatic CRC [77]. The most commonly used chemotherapeutic regimens for CRC are FOLFOX and FOLFIRI [78].…”
Section: Clinical Status Of Irinotecan Combination Therapy In Crcmentioning
confidence: 99%
“…After surgery, chemotherapy can be administered to kill any remaining cancer cells and reduce the risk of cancer recurrence. The National Comprehensive Cancer Network (NCCN) guidelines recommend the use of chemotherapy regimens, including CAPOX (capecitabine and oxaliplatin), FOLFIRI (folinic acid, fluorouracil, and irinotecan), FOLFOX (folinic acid, fluorouracil, and oxaliplatin), or FOLFOXIRI (folinic acid, fluorouracil, oxaliplatin, and irinotecan), for unresectable metastatic CRC [77]. The most commonly used chemotherapeutic regimens for CRC are FOLFOX and FOLFIRI [78].…”
Section: Clinical Status Of Irinotecan Combination Therapy In Crcmentioning
confidence: 99%
“…The results of this study showed no difference in the incidence of thromboembolism (ATE or VTE) between VEGF and EGFR inhibitors, and no difference in the time to thromboembolism, suggesting that the risk of thromboembolism is similar between molecular-targeted therapies. Recently, it has been reported that panitumumab-based chemotherapy is associated with an increased incidence of serious thromboembolism compared to bevacizumab-based chemotherapy [ 18 ]. In this study, the overall incidence of thromboembolism was twice as high in the EGFR inhibitor group, but the possibility of a beta error cannot be ruled out due to the limited number of cases.…”
Section: Main Textmentioning
confidence: 99%
“…Real-world data highlight the complexity of treating RAS-positive CRC, demonstrating that patients with RAS-mutant CRC have a median overall survival ranging from 20 to 30 months when treated with current standard systemic therapies, compared to longer survival in those with RAS wild-type tumors [23]. Furthermore, the adverse effects associated with systemic treatments, including chemotherapy-induced neuropathy and the dermatological toxicities from targeted therapies, can significantly impair patients' quality of life [24,25].…”
Section: Introductionmentioning
confidence: 99%